Motor-language links in children with Down syndrome: a scoping review to revisit the literature with a developmental cascades lens - Karimi, Atefeh; Nelson, Eliza L. (Frontiers in Psychology, 2023)
Background: Children with Down syndrome (DS) typically have motor and language needs. Improving function is a shared goal for the rehabilitation therapy team, however physical therapy, occupational therapy, and speech-language pathology professionals treat patients differently. This difference in care may mask developmental cascades whereby changes in one domain (e.g., motor) can have seemingly unexpected effects on another domain (e.g., language). Objective: This scoping review identified papers where motor and language data have been reported together in children with DS and reinterpreted findings from a developmental cascades lens. Design: Online databases were used to identify 413 papers published before October 2021 from which 33 papers were retained that reported both motor (gross and/or fine) and language (expressive and/or receptive) data in individuals with DS with a chronological age of 0-18 years. Results: The majority of papers (79%) that reported motor and language data in children with DS did not examine their link, while 12% analyzed motor-language links, but using a cross-sectional or retrospective design. Only three papers (9%) utilized a longitudinal design to examine predictive links. Conclusions: Motor functioning and language functioning have often been reported together, but not analyzed together, in studies of children with DS. The few studies that did analyze motor-language links largely replicated findings from other developmental populations where motor gains were positively linked to language gains. Analyzing links between domains when such data is available is needed to fully characterize developmental cascades in DS and may have broad clinical implications.